Nighttime Supplemental LED Inter-lighting Improves Growth and Yield of Single-Truss Tomatoes by Enhancing Photosynthesis in Both Winter and Summer - Tewolde, Fasil T.; Lu, Na; Shiina, Kouta; Maruo, Toru; Takagaki, Michiko; Kozai, Toyoki; Yamori, Wataru (Frontiers in Plant Science, 2016)
Abstract Greenhouses with sophisticated environmental control systems, or so-called plant factories with solar light, enable growers to achieve high yields of produce with desirable qualities. In a greenhouse crop with high planting density, low photosynthetic photon flux density (PPFD) at the lower leaves tends to limit plant growth, especially in the winter when the solar altitude and PPFD at the canopy are low and day length is shorter than in summer. Therefore, providing supplemental lighting to the lower canopy can increase year-round productivity. However, supplemental lighting can be expensive. In some places, the cost of electricity is lower at night, but the effect of using supplemental light at night has not yet been examined. In this study, we examined the effects of supplemental LED inter-lighting (LED inter-lighting hereafter) during the daytime or nighttime on photosynthesis, growth, and yield of single-truss tomato plants both in winter and summer. We used LED inter-lighting modules with combined red and blue light to illuminate lower leaves right after the first anthesis. The PPFD of this light was 165 µmol m-2 s-1 measured at 10 cm from the LED module. LED inter-lighting was provided from 4:00 am to 4:00 pm for the daytime treatments and from 10:00 pm to 10:00 am for the nighttime treatments. Plants exposed only to solar light were used as controls. Daytime LED inter-lighting increased the photosynthetic capacity of middle and lower canopy leaves, which significantly increased yield by 27% in winter; however, photosynthetic capacity and yield were not significantly increased during summer. Nighttime LED inter-lighting increased photosynthetic capacity in both winter and summer, and yield increased by 24% in winter and 12% in summer. In addition, nighttime LED inter-lighting in winter significantly increased the total soluble solids and ascorbic acid content of the tomato fruits, by 20% and 25%, respectively. Use of nighttime LED inter-lighting was also more cost-effective than daytime inter-lighting. Thus, nighttime LED inter-lighting can effectively improve tomato plant growth and yield with lower energy cost compared with daytime both in summer and winter.